The Effect Of Financial Ratio Determinants On Market Share Of Bank Muamalat Indonesia - Septiyanti, Nuratmi Eka; Alam, Syamsu (Program Pascasarjana STIE Amkop Makassar, 2023)
This study aims to examine the determinant effect of financial ratios on the market share of Bank Muamalat Indonesia. Financial ratios are approached by the financing to deposit ratio (FDR), operating expenses and operating income (OEOR), non performing financing (NPF), and capital adequacy ratio (CAR). The observation period in this study is 20 years, from 2003 to 2022. This research uses financial report data issued by Bank Muamalat Indonesia and the publication of the Financial Services Authority (OJK). The data analysis method is multiple linear regression. Before using this method, the data was first tested with the classical assumption tests, namely the normality, heteroscedasticity, multicollinearity, and autocorrelation tests. The results showed that FDR and OEOR had a positive effect on Muamalat Indonesia's market share, while NPF and CAR had no effect. 42.7% of the dependent variables in this study can be explained by independent variables, while the rest are influenced by other factors. Keywords : FDR, OEOR, NPF, CAR, Market share.